Kabuki and CHARGE syndromes: overlapping symptoms and diagnostic challenges - Bruno Pellozo Cerqueira; Elenice Andrade Milhomem; Ana Cristina Carvalho de Matos; Igor Gouveia Pietrobom; Carlos Magno Leprevost; Ita Pfeferman Heilberg (Einstein (São Paulo))
ABSTRACT Kabuki syndrome is a rare congenital malformation with typical facial features, skeletal anomalies, delayed neuropsychomotor development and growth, and cardiac, genitourinary, gastrointestinal, endocrine, and dental anomalies. One of the main differential diagnoses is CHARGE syndrome, standing for and characterized by Coloboma of the eye, Heart defects, Atresia of the nasal choanae, Restricted intellectual development, Genitourinary malformations, and Ear anomalies. Because these syndromes have similar characteristics, distinguishing them may be challenging. A 24-year-old male patient admitted with reduced renal function had a previous phenotype-based diagnosis of CHARGE syndrome based on many characteristic clinical features. The unveiling of a hypocalcemic crisis diagnosed as primary hypoparathyroidism at the age of 15 years, which did not fit into that diagnosis, led the nephrologist to request a genetic test, which evidenced a missense variant of uncertain significance in exon 38 of the KMT2D gene. This phenotype further suggested Kabuki syndrome, ruling out CHARGE. The present report highlights the importance of genetic testing and discusses phenotype-genotype correlations, which ultimately showed that specific variants in exon 38 rendered a form of Kabuki syndrome distinct from the typical one.